Intertextuality and Metafiction in Mark Z. Danielewski’s House of Leave - Ravichandran, Shurman (Journal of Research in Vocational Education, 2026)
Mark Z. Danielewski’s House of Leaves (2000) is a complex, postmodern novel that utilizes intertextuality and metafiction to challenge conventional narrative forms. The novel layers multiple stories within one another, while also heavily referencing other texts, films, and academic traditions. It blurs the boundaries between fiction and reality, forcing readers to question the nature of narrative truth. This paper will analyze how intertextuality and metafiction function in House of Leaves, creating a dense and disorienting experience that reflects the novel’s central themes of space, memory, and psychological